António da Costa Paiva (Barão de Castelo de Paiva) (1806–1879): his malacological collection from Madeira in Universidade de Coimbra, Portugal. Issue 2 (September 2022) - Breves, André; Pereira, Gilberto; Girão Da Cruz, M. Teresa
Abstract : The Museu da Ciência da Universidade de Coimbra (MCUC) (Science Museum of the University of Coimbra) hosts an important historical collection of land and freshwater snails from the Madeira Archipelago. This collection of 1, 768 specimens (120 recent taxa within 20 families) was recently catalogued and digitized. Specimens in MCUC collections were recognized as being provided by António da Costa Paiva (Barão de Castelo de Paiva). This Portuguese nobleman also donated other mollusc collections to different scientific institutions and natural history museums in Portugal and abroad in the mid nineteenth-century. The study of the origin of the MCUC mollusc collection, beyond the data associated with the specimens, is important to the research on the endangered fauna of the Madeira Archipelago. This work precedes a comprehensive study ongoing in MCUC regarding the species occurrence and the systematic review on a great number of species hosted in the museum collection.